Message from the chairman of the Congress Organising Committee - Thornton, Andrew (SA Heart Journal, 2017)
The SA Heart Congress 2011 will be held in East London this year. The programme for this meeting is broad based, with a slight emphasis on rhythm problems, but we have had input from all the special interest groups and there are some parallel sessions. There should be something of interest for everyone who is planning on coming to East London to learn.